1995
DOI: 10.1111/j.1440-1754.1995.tb00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphine increases synchronous ventilation in preterm infants

Abstract: Intravenous morphine infusion increases synchronicity of spontaneous and ventilator-delivered breaths in preterm infants. Morphine reduces heart rate and respiratory rate without reducing blood pressure, and may help to reduce duration of oxygen therapy in preterm infants with hyaline membrane disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 10 publications
1
45
0
2
Order By: Relevance
“…Sedation with midazolam and analgesia with morphine are commonly used and effective to obtain well-tolerated artificial ventilation in preterm infants [1,2] . However, adverse effects of both midazolam and morphine have been described.…”
Section: Introductionmentioning
confidence: 99%
“…Sedation with midazolam and analgesia with morphine are commonly used and effective to obtain well-tolerated artificial ventilation in preterm infants [1,2] . However, adverse effects of both midazolam and morphine have been described.…”
Section: Introductionmentioning
confidence: 99%
“…Esta gran variabilidad ha podido ser detectada gracias a una recogida de datos en la cabecera del paciente; es muy probable que el uso de estas medicaciones no pudiese ser detectado en estudios tipo encuesta. De forma similar, Jenkins et al, en un estudio prospectivo de 338 pacientes pediátricos (incluyendo 39 neonatos) de 20 unidades en Reino Unido, reportan 24 fármacos sedantes o analgésicos distintos 32 . Es fácil concluir que estas diferencias entre unidades dificultan la comparación de resultados y el estudio de la S/A en nuestro país.…”
Section: Discussionunclassified
“…Nonetheless, the propensity score matching was used with the aim of minimising bias created by baseline characteristics. Discussion about opioid use in ventilated neonates include developmentally regulated pain sensitivity, clinical instability from acute pain or stress, unsynchronised breathing, and suboptimum ventilation, 32 and long-term eff ects on brain development. [33][34][35][36] A Cochrane review concluded that opioids reduce neonatal pain scores, and do not prolong ventilation, alter mortality or subsequent intelligence, motor function, or behaviour, 33 but evidence for the routine treatment of ventilated newborn babies with opioids is insuffi cient.…”
Section: Discussionmentioning
confidence: 99%
“…54,75,76,88,116,123,124 Numerous randomized, controlled trials have evaluated pain control in mechanically ventilated newborns, but many have been underpowered. 19,39,102,[125][126][127][128] Two recent appropriately powered studies enrolled a total of 1048 neonates and demonstrated no differences in the incidence of severe intraventricular hemorrhage, periventricular leukomalacia, or death outcomes between the ventilated infants who received morphine or placebo infusions. 122,124 Pain assessments during tracheal suctioning were unaltered in 1 trial 124 and minimally diminished in the other trial.…”
Section: Procedural Painmentioning
confidence: 99%
“…90,99 Future studies should examine the influence of administration of perioperative analgesics on the duration of assisted ventilation required, the timing of extubation, and overall respiratory function. [100][101][102] General anesthesia includes achieving unconsciousness (lack of implicit recall and lack of awareness of surgery), analgesia, suppression of autonomic responses to noxious stimuli, and immobility. Studies using general anesthesia in the pediatric age group need to address whether newer agents are safer in the short-term than existing agents and investigate their immediate and long-term postoperative outcomes.…”
Section: Procedural Painmentioning
confidence: 99%